Akkermansia muciniphila regulates the gut microenvironment and alleviate periodontal inflammmation in mice with periodontitis - Zhang, Shumin; Zhang, Ting; Zhang, Yiwen; Ye, Chuanjin; Mu, Litong; He, Qinghui; Huang, Tianxiang; Wang, Guowei; Li, Yanan; Xie, Sijing; Tang, Xuna (Frontiers in Microbiology, 2025)
ObjectiveAkkermansia muciniphila (A. muciniphila) is an emerging gut commensal known for its roles in host metabolism and immune modulation. While its involvement in metabolic and inflammatory disorders is well characterized, its potential association with oral diseases such as periodontitis remains poorly understood. This study aimed to explore whether modulation of the gut microbiota via fecal microbiota transplantation (FMT) from periodontally healthy donors could influence the abundance of A. muciniphila and contribute to the alleviation of periodontitis.MethodsFecal samples were collected from human donors, including periodontally healthy individuals (H group, n = 16), untreated patients with severe periodontitis (P group, n = 12), and the same patients at two weeks (P2W) and three months (P3M) after periodontal therapy. Quantitative PCR was used to assess A. muciniphila abundance in these human samples. A germ-free mouse model of periodontitis was then established, and the mice received FMT using samples from human donor groups (P-PBS, P-H, and P-P). Gut microbiota composition, periodontal inflammation, gut barrier proteins (MUC2, ZO-1), and inflammatory cytokines (IL-6, TNF-α) were evaluated in the mice.ResultsCompared to groups H, P2W, and P3M, the abundance of A. muciniphila in the gut was significantly lower in patients with severe periodontitis, but it was increased after periodontal therapy. In mice, FMT from healthy donors (P-H group) significantly enriched A. muciniphila, improved expression of gut barrier proteins, reduced inflammatory cytokine levels, and alleviated periodontal inflammation compared to other groups.ConclusionThese findings suggest a previously underrecognized link between gut microbial composition particularly A. muciniphila and periodontal health. Targeting the gut microbiota via FMT may represent a novel strategy for modulating systemic and oral inflammation and supporting the prevention or adjunctive treatment of periodontitis.